Effects of potential detoxifying agents on growth performance and deoxynivalenol (DON) urinary balance characteristics of nursery pigs fed DON-contaminated wheat - Frobose, Hyatt L.; Stephenson, E. W.; Tokach, Michael D.; DeRouchey, Joel M.; Woodworth, Jason C.; Dritz, Steven S.; Goodband, Robert D. (My University, 2017)
Two experiments were conducted to evaluate potential detoxifying agents on growth of nursery pigs fed deoxynivalenol (DON)-contaminated diets. Naturally DON-contaminated wheat (6 mg/kg) was used to achieve desired DON levels. In a 21-d study, 238 pigs (13.4 +/- 1.8 kg BW) were used in a completely randomized design with a 2 x 2 + 1 factorial arrangement. Diets were: 1) Positive control (PC; < 0.5 mg/kg DON), 2) PC + 1.0% Product V (Nutriquest LLC, Mason City, IA), 3) Negative control (NC; 4.0 mg/kg DON), 4) NC + 1.0% Product V, and 5) NC + 1.0% sodium metabisulfite (SMB; Samirian Chemicals, Campbell, CA). There were 6 or 7 replicate pens/treatment and 7 pigs/pen. Analyzed DON was decreased by 92% when pelleted with SMB, but otherwise matched formulated levels. Overall, a DON x Product V interaction was observed for ADG (P < 0.05) with a tendency for an interaction for ADFI (P < 0.10). As anticipated, DON reduced (P < 0.001) ADG and ADFI, but the interaction was driven by even poorer growth when Product V was added to NC diets. Pigs fed NC diets had 10% poorer G: F (P < 0.001) than PC-fed pigs. Reductions in ADG due to DON were most distinct (50%) during the initial period. Adding SMB to NC diets improved (P < 0.01) ADG, ADFI, and G: F, and improved (P < 0.02) ADG and G: F compared to the PC diet. A urinary balance study was conducted using diets 3 to 5 from Exp. 1 to evaluate Product V and SMB on DON urinary metabolism. A 10 d adaptation was followed by a 7 d collection using 24 barrows in a randomized complete block design. Pigs fed NC + SMB diet had greater urinary DON output (P < 0.05) than pigs fed NC + Product V, with NC pigs intermediate. Daily DON excretion was lowest (P < 0.05) in the NC + SMB pigs. However, degradation of DON-sulfonate back to the parent DON molecule was observed as pigs fed NC + SMB excreted more DON than they consumed (164% of daily DON intake), greater (P < 0.001) than pigs fed the NC (59%) or NC + Product V (48%). Overall, Product V did not alleviate DON effects on growth nor did it reduce DON absorption and excretion. However, hydrothermally processing DON-contaminated diets with 1.0% SMB restored ADFI and improved G: F. Even so, the urinary balance experiment revealed that some of the converted DON-sulfonate can degrade back to DON under physiological conditions. While further research is needed to discern the stability of the DON-sulfonate, SMB appears promising to restore performance in pelleted DON-contaminated diets.
Citation: Frobose, H. L., Stephenson, E. W., Tokach, M. D., DeRouchey, J. M., Woodworth, J. C., Dritz, S. S., & Goodband, R. D. (2017). Effects of potential detoxifying agents on growth performance and deoxynivalenol (DON) urinary balance characteristics of nursery pigs fed DON-contaminated wheat. Journal of Animal Science, 95(1), 327-337. doi:10.2527/jas2016.0664
Keywords: Adsorbents; Deoxynivalenol; Mycotoxins; Nursery Pigs; Sodium; Metabisulfite